2021
DOI: 10.3390/computers10020018
|View full text |Cite
|
Sign up to set email alerts
|

Network Analysis of Local Gene Regulators in Arabidopsis thaliana under Spaceflight Stress

Abstract: Spaceflight microgravity affects normal plant growth in several ways. The transcriptional dataset of the plant model organism Arabidopsis thaliana grown in the international space station is mined using graph-theoretic network analysis approaches to identify significant gene transcriptions in microgravity essential for the plant’s survival and growth in altered environments. The photosynthesis process is critical for the survival of the plants in spaceflight under different environmentally stressful conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…We have also shown how topological network measures of degree distribution are useful for the extraction of subnetwork modules from larger GRNs. The subnetworks sampled from the original GRNs also have a scale-free topology with a degree distribution that follows an exponential power law [ 54 ]. Centrality measures are useful for distinguishing protein complexes [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have also shown how topological network measures of degree distribution are useful for the extraction of subnetwork modules from larger GRNs. The subnetworks sampled from the original GRNs also have a scale-free topology with a degree distribution that follows an exponential power law [ 54 ]. Centrality measures are useful for distinguishing protein complexes [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Graph-based Gene Regulatory Network (GRN) inferencing methods of Pearson correlation and Markov Blanket (MB) are utilized to identify the most regulated genes in the seven GeneLab datasets [ 17 , 18 ]. The gene expression values of pairs of genes are used to compute the Pearson correlation value.…”
Section: Methodsmentioning
confidence: 99%
“…It has been proved by Vaulina et al (1984) that spaceflight can cause chromosome aberration, gene deletion and recombination of crops, thus causing genetic material variation. Moreover, crops adapted to the effects of spaceflight by adjusting their own metabolic network ( Paul et al, 2017 ), which was induced by oxidative stress and heat stress ( Manian et al, 2021 ). The current research conclusions showed that spaceflight has caused changes in plant lipid peroxidation, antioxidant enzymes, energy metabolism, signal transduction, protein synthesis, cell wall biosynthesis and other processes ( Matía et al, 2010 ; Ferl et al, 2015 ; Choi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%